Drug-induced sarcoid-like reaction during BRAF/MEK inhibitor therapy for metastatic melanoma - A.N. Khlebnikova; V.E. Shikina; A.V. Semenkov; A.I. Zotov; G.R. Setdikova (Russian Journal of Clinical Dermatology and Venereology, 2026)
In recent years, targeted therapy with BRAF/MEK inhibitors has been successfully used for treating metastatic melanoma. Although generally well tolerated, it may lead to the development of both systemic and cutaneous side effects. The most frequently reported adverse events include nausea, vomiting, diarrhea, pyrexia, chills, and hypertension. Cutaneous side effects manifest as alopecia, acneiform rash, maculopapular rash, dry skin, and photosensitivity reactions. Cases of squamous cell carcinoma and keratoacanthoma development are described. Rare adverse events include the development of drug-induced sarcoid-like reactions, which usually manifest as granulomatous dermatitis; less commonly, a combination of cutaneous manifestations with systemic lesions is observed. We present a case report of a patient with metastatic melanoma receiving therapy with BRAF/MEK inhibitors. After 3 years and 4 months of targeted therapy, she developed cutaneous eruptions on the upper extremities and trunk, which were morphologically characterized as sarcoid-like granulomas. At the 1-year follow-up, histologically confirmed sarcoid-like granulomas were identified in the lungs and mediastinal lymph nodes. The manifestations were assessed as a systemic drug-induced sarcoid-like reaction. The patient continued targeted therapy (dabrafenib 150 mg twice daily and trametinib 2 mg once daily), and topical corticosteroids were recommended. The patient is currently being followed by an oncologist, dermatovenereologist and pulmonologist.